Beef assessments using functional magnetic resonance imaging and sensory evaluation. (April 2017) - Tapp, W.N.; Davis, T.H.; Paniukov, D.; Brooks, J.C.; Brashears, M.M.; Miller, M.F.
Abstract: Functional magnetic resonance imaging (fMRI) has been used to unveil how some foods and basic rewards are processed in the human brain. This study evaluated how resting state functional connectivity in regions of the human brain changed after differing qualities of beef steaks were consumed. Functional images of participants (n = 8) were collected after eating high or low quality beef steaks on separate days, after consumption a sensory ballot was administered to evaluate consumers' perceptions of tenderness, juiciness, flavor, and overall liking. Imaging data showed that high quality steak samples resulted in greater functional connectivity to the striatum, medial orbitofrontal cortex, and insular cortex at various stages after consumption ( P ≤ 0.05). Furthermore, high quality steaks elicited higher sensory ballot scores for each palatability trait ( P ≤ 0.01). Together, these results suggest that resting state fMRI may be a useful tool for evaluating the neural process that follows positive sensory experiences such as the enjoyment of high quality beef steaks.